Digitalization and smartening sustainable city development: an investigation from the high north European cities - De Melo Cartaxo, T; Castilla, JM; Dymet, M; Hossaik, K (Faculty of Public Administration, National University of Political Studies & Public Administration, Romania, 2021)
This is the final version. Available from the Faculty of Public Administration, National University of Political Studies & Public Administration via the DOI in this record. The European High North (EHN) region faces distinct challenges in terms of socio-economic, cultural and environmental infrastructure. As a peripheral region, it is usually characterised as being geographically distant, with a sparse population, relatively poor physical and economic infrastructure, and far from major administrative hubs located mostly in its southern areas. Integrating new technology as a well-established phenomenon, particularly digital innovation, in regional development strategies has been found enormously relevant and beneficial for the citizens inhabiting this region. In effect, the EHN’s sustainability depends on the efficient management of land use and natural resources, economic and human activities, and services and facilities. The expansion of digital technology and its appearance in many areas of the everyday lives of people and communities provide better efficiencies in the context of service design and infrastructural development. Given that the EHN is relatively better progressed than similar peripheral regions and has therefore set an example of modern development in the area of digitalisation, this paper analyses the realities of the cities of Tromsø in Norway and Rovaniemi in Finland as case studies of providing potentially ‘smarter’, efficient, and modern services that combine development, sustainability, and human wellbeing. Nordforsk